Constructing SHiP and an International Historical Coding System for Causes of Death - Janssens, Angélique (Historical Life Course Studies, 2021)
SHiP is a network of European researchers studying mortality dynamics in port cities across Europe in the 19th and 20th centuries. All members make use of unique individual-level cause-of-death data for roughly the period 1850–1950 which allows the study of mortality to move beyond what was captured in nineteenth-century highly-aggregated national statistics. Apart from registering the individual cause of death, most datasets provide a wealth of information, such as name and address of the deceased, date of death, his/her age, sex, marital status, and religion and occupation of the deceased. Port cities are viewed as 'gateways of disease' in the same way that airports today function as hubs for the transmission of infectious diseases. The SHiP network aims to study the particular epidemiological profiles of the port cities in a truly comparative fashion across the different European maritime areas. To that end the SHiP team members have embarked upon the construction of a joint coding scheme, called ICD10h, which assigns codes to a large number of causes of death in a systematic way. Its main features are that the ICD10h coding scheme can deal well with large numbers of historical disease descriptions, from different linguistic areas in Europe, while at the same time it is able to connect to current day disease patterns.